THE CLASSIFICATION AND THE EVALUATION OF THE MANAGEMENT CONSULTING METHODS - T. V. Chibikov (Вестник СибАДИ)
This research is relevant, because management consulting is a popular, growing activity and its demand grows each year. The article presents the  management advice methods’ classification based on the consultation  process’ stages. The special features of the consulting methods are  determined. Also the main groups and types of the management consulting  methods are identified. The conclusion about the necessity of the methods’  improving and management consulting techniques’ innovations in the  Russian market is made. The existing methods of efficiency evaluation in the  diversity terms of possible outcomes consulting services are viewed. The practical significance of the research  concludes in the possible applying of the proposed classifications in the  consulting services’ development, as well as in the results of the services effectiveness’ evaluation.